The Effect of Calendula officinalis on Oxidative Stress and Bone Loss in Experimental Periodontitis - Lima, Mariana dos Reis; Lopes, Amanda P.; Martins, Conceição; Brito, Gerly A. C.; Carneiro, Virgínia C.; Goes, Paula (Frontiers in Physiology, 2017)
Periodontitis is associated with reduced antioxidant capacity and increased oxidative damage. Oxidative stress induces inﬂammation and bone loss contributing to the pathological progression of periodontal disease. Calendula officinalis (CLO) has demonstrated anti-inflammatory and anti-oxidant activities. Therefore the aim of this study was to evaluate the effect of CLO on oxidative stress and bone loss in rats subjected to experimental periodontitis (EP). For this, 72 male Wistar rats were divided into groups: Naïve, Saline (SAL) and CLO. Rats received SAL or CLO (90 mg/kg) 30 minutes before ligature and daily until the 11th day. Naïve group experienced no manipulation. After 11 days, the animals were euthanized and left maxillae collected for macroscopic analysis of alveolar bone loss (ABL). Periodontium was analyzed by macroscopy, scanning electron microscopy; confocal and light polarized microscopy. Immunohistochemical examination of DKK1, WNT 10b and β-catenin was performed. The gingival tissue was collected to reduced glutathione (GSH), superoxide dismutase (SOD), catalase (CAT) and malondialdehyde (MDA) analyses. The 11 days of ligature induced bone loss, breakdown of collagen fibers, increased the immunostaining DKK-1 while reduced WNT 10b and β-catenin expressions. Periodontitis reduced GSH, SOD, CAT and increase MDA. All findings were reversed by 90 mg/kg of CLO. In summary our findings demonstrated that CLO reduced oxidative stress and bone loss and preserved collagen fibers in rats with EP, with participation of WNT signaling pathway.